Determinants of Stock Volatility of Indonesian State-Owned Enterprises on the Indonesia Stock Exchange: A Panel-Data Modelling Approach with Firm Size as a Moderating Variable - I Dewa Made Tirta Meirsha; I Gusti Ketut Agung Ulupui; Adler Haymans Manurung (Journal of Applied Data Sciences, 2026)
This study examines the determinants of stock-price volatility among Indonesian State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) and tests whether Firm Size (FS) moderates these relationships. Five groups of explanatory features are integrated into a single model: macro fundamentals (MF), micro fundamentals (MiF), capital structure measured by Government Funding (GF), Stock-Market Volatility (SMV), and Market Liquidity (ML). Using a balanced panel of 24 listed SOEs over 2019–2024 (144 firm-year observations), model selection across common-, fixed-, and random-effects specifications identifies the Common Effects Model (CEM) as the most appropriate. The model is jointly significant (Prob. F = 0.0001) and explains 40.37% of the variation in volatility (R2 = 0.4037). The findings reveal that inflation (β = -29.412, p = 0.022), the debt-to-equity ratio (β = -0.9996, p = 0.035), return on assets (β = -1.6373, p = 0.011), and government funding (β = -0.0197, p = 0.002) each significantly and negatively shape stock volatility. Broad market volatility and trading volume are statistically insignificant. Furthermore, firm size significantly moderates the exchange rate effect (β = 5.1933, p = 0.003) and the return on assets effect (β = -0.4727, p = 0.023). This paper contributes to literature by offering a unified, data-driven framework and extending efficient-market, behavioural-finance, and trade-off theories to state ownership, demonstrating that state-backed funding acts as a stabilizing capital component rather than a risk driver. Practical recommendations for the Ministry of SOEs include establishing performance-linked funding benchmarks and public-service account separation to mitigate market distortions and stock volatility.